2022
DOI: 10.28991/esj-2022-sper-011
|View full text |Cite
|
Sign up to set email alerts
|

Mayoral Influence on Participatory Budgeting in Lithuania during Covid-19

Abstract: The paper deals with two topics: Participatory Budgeting (PB) and mayoral impact on its success. Its theoretical background is rooted in the interrelation of the discourse of PB and characteristics of mayors as city leaders. The paper analyzes articles revealing personal, social and political characteristics of mayors and their impact on civic governance. The scope of collected characteristics was researched with a view on how they impact succession and the resilience of PB. The idea behind this analysis was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
2
0
2
Order By: Relevance
“…Además, es en los municipios gobernados por partidos más a la izquierda donde la valoración de la gravedad del impacto es mayor en comparación con los municipios en los que gobiernan partidos de centroizquierda, centro y derecha. Esto conecta con otros estudios como Burkšienė et al (2022), que destacan la importancia de la afiliación política a la hora de conseguir mecanismos participativos resilientes que resistan en momentos de crisis.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Además, es en los municipios gobernados por partidos más a la izquierda donde la valoración de la gravedad del impacto es mayor en comparación con los municipios en los que gobiernan partidos de centroizquierda, centro y derecha. Esto conecta con otros estudios como Burkšienė et al (2022), que destacan la importancia de la afiliación política a la hora de conseguir mecanismos participativos resilientes que resistan en momentos de crisis.…”
Section: Discussionunclassified
“…En el caso de los presupuestos participativos, según el informe Atlas, hasta un 55 % fueron cancelados a causa de la pandemia (Dias et al, 2021). La decisión de paralizar totalmente las iniciativas fue adoptada por la falta de recursos, ya que en épocas de crisis su asignación se ve claramente afectada (Burkšienė et al, 2022). Encontramos ejemplos de presupuestos participativos que sufrieron la paralización total a causa de la COVID-19 en todo el mundo, desde Halifax en Canadá, pasando por Nueva York y Vallejo en Estados Unidos, hasta Gdansk en Polonia (íd.).…”
Section: Introductionunclassified
“…The government of Lithuania introduced a total quarantine on March 16, 2020 [38], which lasted three months until June 17, 2020. Quarantine measures were complex and included restriction of movement across borders and within the country; maximal transition to remote work (if possible); restricted operation of shopping malls, restaurants, bars, and beauty salons (except for grocery stores and pharmacies); sudden transition to remote education in kindergartens, schools, and universities; and prohibition of activities in daycare facilities and other centres for children, people with disabilities, and older adults [39]. Wearing face masks and disinfecting hands were required when using public spaces.…”
Section: -2-the Covid Pandemic Crisis In Lithuaniamentioning
confidence: 99%
“…Lithuanian politicians were proud that they handled the first COVID-19 wave rather well. However, significant consequences were experienced by people in terms of working life [39,40], income maintenance [41], and mental health [42,43]. A study commissioned by Luminor Bank showed that 6% of adult Lithuanian citizens lost their jobs during the first quarantine, and 14% had to take compulsory or temporary leave [44].…”
Section: -2-the Covid Pandemic Crisis In Lithuaniamentioning
confidence: 99%